Rapid and Systemic Accumulation of Chloroplast mRNA-Binding Protein Transcripts after Flame Stimulus in Tomato - Vian, Alain (American Society of Plant Physiologists, 1999)
It has been shown that tomato (Lycopersicon esculentum) plants respond to flame wounding and electrical stimulation by a rapid (15 min) and systemic up-regulation of proteinase inhibitor (pin) genes. To find other genes having a similar expression pattern, we used subtractive cDNA screening between flamed and control plants to select clones up-regulated by flame wounding. We report the characterization of one of them, a chloroplast mRNA-binding protein encoded by a single gene and expressed preferentially in the leaves. Systemic gene expression in response to flaming in the youngest terminal leaf exhibited three distinct phases: a rapid and transient increase (5–15 min) in transcript accumulation, a decline to basal levels (15–45 min), and then a second, more prolonged increase (60–90 min). In contrast, after a mechanical wound the rapid, transient increase (5 min) was followed by a rapid decline to basal levels but no later, prolonged accumulation. In the petiole, the initial flame-wound-evoked transient increase (15 min) was followed by a continuous decline for 3 h. The nature of the wound signal(s) causing such rapid changes in transcript abundance is discussed in relation to electrical signaling, which has recently been implicated in plant responses to wounding.